Neurological manifestations of COVID-19: a clinical approach (Medical Journal of Indonesia, 2021)
Coronavirus disease 2019 (COVID-19) is an emerging infectious disease caused by SARS-CoV-2 which attacks the respiratory tract and has been declared a global pandemic by the World Health Organization. The disease has a very wide clinical spectrum which can be manifested as asymptomatic to critical conditions. SARS-CoV-2 shows a neurotropism proven by its identification in the cerebrospinal fluid and brain vascular endothelial. The complete mechanism of how the virus invades the human nervous system is yet to be identified. Thus, every neurologist needs to follow the progressivity of COVID-19 symptoms involving the nervous system.